Gamelan Serdang collection re-creation - Jahnichen, Gisa; Musib, Ahmad Fauzi (Universiti Putra Malaysia Press, 2011)
Originally, the repertoire was thought to be played as an exercise in sight reading, improvisation and arrangement. Simple melodic cycles employing a choice of 3-5 pitches serve as basic material, some of them reflect patterns taken from local dance melodies. Metric versatility and rhythmic structuring individually planned for each instruments of the gamelan make a great part of the entire composition that is achieved through team work during the rehearsals. Well discussed introductions and transitions in various phases of each piece contribute to the individuality of the repertoire. Tempo and dynamics are very important due to the fact that performances of one and the same gamelan over a certain time period often suffer from the limitation in tuning and the impossibility of transposition. Though gamelan cultures, especially in Indonesia, can traditionally provide essential changes in mood and character through an enormous amount of multi-layered and metro-rhythmic features, gamelan playing in Malaysia cannot yet rely on an audience equally educated in musical perception of gamelan music that could appreciate small rhythmic differences and stylistic refinements in repetitive musical structures. Therefore, the repertoire can be seen as a collection of mostly modern compositions applying traditional production patterns and improvisatory forms of musical communication in a popular way.